PENGEMBANGAN BUDAYA ORGANISASI BERBASIS KINERJA DALAM PENINGKATAN MUTU PENDIDIKAN - Fara Fariha Rodliyana; Samas Muizul Mala (Al Arsy: Journal of Education, Management and Islamic Thought, 2026)
SMP Islam Gandusari in Trenggalek Regency faces challenges related to educational quality, as evidenced by fluctuations in teacher attendance and disparities in student competency achievement. This study aims to explore how the development of a performance-based organizational culture can improve teacher discipline, teacher performance, and learning quality at the school. The research focuses on the characteristics of the performance culture before and after the intervention, the impact of the performance culture on teachers and students, as well as the supporting and inhibiting factors in its implementation. The study employs a qualitative approach through field-based case study research. Data were collected through participatory observation, semi-structured interviews with the principal, teachers, and educational staff, as well as analysis of school documents. This approach enables a contextual understanding of work culture practices, internal interactions, and organizational dynamics that influence educational quality. The findings indicate that the implementation of a performance-based organizational culture at SMP Islam Gandusari enhanced teacher discipline and productivity through clear performance standards, reward and punishment mechanisms, routine supervision, and consistent team collaboration. Learning quality improved through more varied instructional methods, the use of digital media, and increased student active participation. The quality of school administrative services also became more orderly, efficient, and responsive, strengthening institutional accountability and community satisfaction. The success of the implementation was shaped by visionary leadership, teacher commitment, and support from the school committee and the broader community, while resistance to change, limited access to digital facilities, and administrative workload remained significant barriers.